Estimation of estuarine habitat degradation and its influence on the reproduction process of the crab Eriocheir sinensis in the Yangtze River Estuary - Tingting Zhang; Nan Du; Zhi Geng; Sikai Wang; Yu Gao; Gang Yang; Xiaorong Huang; Tao Zhang; Ping Zhuang; Feng Zhao (Ecological Processes, 2023)
Abstract Background The provision of habitat for fishery species in estuaries is highly valued and represents one of the most challenging ecosystem service values to quantify. However, quantifying this value is challenging due to complex relationships between habitat change, ecological processes, and environmental variations. This study aims to estimate estuarine habitat degradation and its impact on the reproduction process of the crab Eriocheir sinensis by characterizing the changes in breeding habitat and investigating relationships between the species and its habitat in the Yangtze River Estuary. Methods A species distribution model recently developed was applied to estimate the extent and quality of breeding habitat changes from 2014–2021. The intrinsic (physiological) and external (structural) reproductive attributes of the breeding process were measured to assess the effects of habitat change. The relationships among habitat change, reproductive attributes and environmental factors were analyzed to understand the underlying driving forces of habitat degradation for breeding process by multivariate statistical analysis. Results About 34.24% of essential habitat was lost, mainly in highly suitable areas due to reclamation and waterway construction. Habitat degradation significantly affects female distribution and their reproductive processes, particularly gonad development during the pre-reproductive period and fecundity during the reproductive period, without altering population structure. These results indicated that the main ecological function served by the highly suitable breeding ground was the provision for development of gonad and improvement of fecundity. Increases of salinity and turbidity, caused by hydrodynamic changes from large-scale waterway construction, were identified as the environmental determinants contributing to cumulative habitat degradation. These influences ultimately led to a decrease in the fecundity of E. sinensis. Conclusions Our research sheds light on the quantification of habitat degradation in the Yangtze River Estuary and its implications for the reproduction process of E. sinensis, which can serve as a foundation for assessing and quantifying the ecosystem service values provided by these breeding grounds. This information is valuable for policymakers and resource managers in making informed decisions regarding habitat conservation and the sustainable utilization of fishery resources.